Neuropsychiatric adverse drug reactions with oral tyrosine kinase inhibitors in metastatic colorectal cancer: an analysis from the FDA Adverse Event Reporting System - Barbieri, Maria Antonietta; Russo, Giulia; Sorbara, Emanuela Elisa; Cicala, Giuseppe; Franchina, Tindara; Santarpia, Mariacarmela; Speranza, Desirèe; Spina, Edoardo; Silvestris, Nicola (Frontiers in Oncology, 2023)
Introduction: New oral tyrosine kinase inhibitors (TKIs) are approved for metastatic colorectal cancer (mCRC). The aim of this study was to assess the neuropsychiatric adverse drug reactions (ADRs) of these drugs reported in the FDA Adverse Event Reporting System (FAERS) database. Methods: All reports with regorafenib (REG) and encorafenib (ENC) as the primary suspect, and reported in the FAERS between 2012 and 2022, were collected. A descriptive and disproportionality analyses were conducted. Results: Out of 4,984 cases, 1,357 (30.2%) reported at least one neuropsychiatric ADR. New potential signals for REG included neuropathy peripheral (n = 265; reporting odds ratio, ROR = 19.48, 95% confidence interval, CI 95% = 17.52-22.47; information component, IC = 2.89, IC025-IC075 = 2.77-3.02), hyperesthesia (n = 18; ROR = 12.56, CI 95% = 7.90-19.96; IC = 2.25, IC025-IC075 = 1.79-2.72), taste disorder (n = 41; ROR = 9.91, CI 95% = 7.29-13.49; IC = 2.18, IC025-IC075 = 1.88-2.49), poor quality sleep (n = 18; ROR = 6.56, CI 95% = 4.13-10.42; IC = 1.74, IC025-IC075 = 1.27-2.20), altered state of consciousness (n = 15; ROR = 5.50, CI 95% = 3.31-9.14; IC = 1.57, IC025-IC075 = 1.06-2.07), depressed mood (n = 13; ROR = 1.85, CI 95% = 1.07-3.19; IC = 0.58, IC025-IC075 = 0.04-1.13) and insomnia (n = 63; ROR = 1.48, CI 95% = 1.15-1.89; IC = 0.38, IC025-IC075 = 0.13-0.63). For ENC comprised depressed mood (n = 4; ROR = 5.75, CI 95% = 2.15-15.39; IC = 1.74, IC025-IC075 = 0.76-2.73) and cognitive disorders (n = 3; ROR = 4.71, CI 95% = 1.51-14.66; IC = 1.54, IC025-IC075 = 0.41-2.68). Discussion: This study identified new unknown potential neuropsychiatric ADRs. Further investigations are required to better define the neurotoxicity of TKIs in mCRC patients.